THE EFFECT OF PRODUCT QUALITY AND WARDAH SKINCARE BRAND TRUST ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION - Utama, Siswono Yoga; Susila, Ihwan (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The purpose of this study was to analyze the effect of product quality and Wardah Skincare brand trust on customer loyalty mediated by customer satisfaction. The type of research used in this study is quantitative. The data source for this research is primary data. The population in this study were all people and all Indonesian people. The sampling technique in this study was Non-probability Sampling. The sample used in this study was 120 respondents. The data collection method uses a closed questionnaire type. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The results of this study are that product quality has a positive and significant effect on customer satisfaction. Brand trust has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer loyalty. Brand trust has a positive and significant effect on customer loyalty. Customer satisfaction significantly mediates product quality on customer loyalty. Customer satisfaction significantly mediates the relationship between brand trust and customer loyalty.